A global learning-centered approach to higher education: workplace development in the 21st century - Carlos Tasso Eira de Aquino; Robert W. Robertson; Pamela Allen; Paul Withey (Centro de Estudios Financieros, 2017)
Competition in the 21st century economy requires corporations, organizations, and professionals to face a common challenge: diverse individuals need consistent motivation towards building competences that increase personal marketability using a combination of higher education and professional development. This article represents an evolving report summary and non-traditional learning-centered approach focusing on adult competences necessary for succeeding in the competitive global marketplace of the 21st century. The purpose of this article is to understand the needs of constantly changing employer demands in the work environment. Exploring contemporary approaches related to skill development, adult education, and learning processes, will be the path towards higher levels of professional success. This article will provide readers with an enlightening discussion focusing on the necessary adult skills and competencies professionals need to succeed in the global marketplace.